THE EFFICIENCY OF LOCAL ENDOSCOPIC INJECTION THERAPY IN ACUTE UPPER GASTROINTESTINAL HEMORRHAGE DUE TO PEPTIC ULCERS - Nadir YÖNETİCİ,; Ahmet AYDIN,; Ömer ÖZÜTEMİZ,; Ahmet MUSOĞLU,; Yücel BATUR,; Hanefi ÇAVUŞOĞLU, (Turkish Journal of Gastroenterology, 2020)
-